Prospek Kontribusi DAS Cikapundung Memenuhi Laju Permintaan Sumber Air Baku Metropolitan Bandung - Sabar, Arwin (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
Among major problems occurring in urban development, the most critical issue is the limitation of water resources as raw water for drinking water supply, especially its existing quantity. The groundwater contribution to fulfil raw water requirements in metropolitan bandung is realatively decreasing, The Cikapundung River, is an alternative source for raw water, is being used as primary raw water for several decades in Bandung. Using statistical method, research has shown that the distribution of minimum flow of the three flow stations could not meet the total demand in dry months. Station Cigulung-Maribaya, Station Cikapundung-Maribaya, and Cikapundung-Gandok usually experienced an extreme dry condition in September. The minimum flows for those three stations for a 20 years repeating period are 0.226 m3/sec, 0.893 m3/sec and 0.336 m3/sec, respectively. The dam that has been constructed up stream of The Cikapundung River is expected to increase the capacity of Station Maribaya up to 0.608 m3/sec, which could then impact the total raw water supply for Pakar Water Treatment Plant. Concurrently, the construction of dam at Station Gandok is targeted to increase the raw water supply up to 0.604 m3/sec. Those means giving solution for migrating groundwater to surface water utilization.Keywords: daily minimum flow, monthly minimum flow, reservoirPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3944[How to cite: Sabar, A., 2006, Prospek  Kontribusi  DAS Cikapundung  Memenuhi Laju  Permintaan Sumber  Air Baku  Metropolitan Bandung, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 169-178]